PENGARUH MEDIA EXPOSURE, KINERJA KEUANGAN, DAN TAX AVOIDANCE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Ninnu Rachim, (2021)
This study uses quantitative methods that aim to examine the relationship between media exposure, financial performance, and tax avoidance on corporate social responsibility disclosure. Corporate social responsibility as dependent variable is measured by Corporate Social Resposibility Disclosure (CSRD) accordance with GRI 91 indicators. This study uses data from companies listed in Indonesia Stock Exchange (IDX) 2017-2019. Sampling uses a purposive sampling method with 123 samples on the Indonesia Stock Exchange (IDX). Tested of hypothesis in this study using multiple linear regression with software SPSS. The results of this study indicated are media exposure, financial performance, and tax avoidance has no effect on corporate social responsibility disclosure.